PENGARUH STATUS SOSIAL ORANG TUA TERHADAP MOTIVASI ANAK UNTUK SEKOLAH PADA PERGURUAN TINGGI - Sirilius Seran (Jurnal Pendidikan Ekonomi (Economic Education Journal), 2016)
The purpose of this research was to determine the relationship between socio-economic variables of parents and the motivation of students to study in college. Number of dependents and family support stand as intermediate variable, which connects to theanother one, namely student motivation. The subject of this research was the high school students of class 11, and 12 including their parents in three regencies: Belu, TTU, and TTS. Using path analysis showed that there is a positive relationship between education, employment, income, and savings and the motivation of students. Variable of number of dependents have negative relationship but are significant with motivation of students. It also happened when the testing was done through the intermediate variable (indirect relation), that only a dependent and the family support variables have negative relationship with the motivation of students. Keywords: social status and motivation